Static and Live Digital Forensics, along with practical examples of tools used for each approach (Texas Journal of Engineering and Technology, 2023)
The field of digital forensics involves examining and analyzing data, with computers being a primary means of communication that investigators can use to gather relevant information. Forensic analysis can be conducted in either a static or live mode. While the traditional static approach may provide incomplete evidence, live analysis tools offer a more precise and consistent view of current and previous processes. Certain critical system-related data stored in volatile memory cannot be effectively retrieved with static analysis techniques. This paper provides a brief overview of both static and live analysis methods and outlines various tools and techniques utilized in digital forensic analysis.